Nurse’s Knowledge, Practices, And Perceived Barriers Towards Care of Pressure Ulcers. - Chopade, Ujawala; Jagatap, J.M.; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
Introduction- Pressure ulcer lead to agony and inconvenience for patients and furthermore cause draw out sickness, defer rebuilding, increment patient’s emergency clinic remain, and may prompt illness and even death. The purpose of this study was to assess the nurse’s knowledge and practices and barriers of pressure ulcer prevention and management. Methodology: A cross sectional quantitative descriptive study among 200 nurses conducted in tertiary care Hospital karad. The study members were chosen by convenience sampling method. An adopted questionnaire circulates among study members. Data entered and analyzed in SPSS for descriptive statistics and results presented in Graphs and Tables. Results: Nurses have average knowledge (55.9%) 53.6% nurses using their knowledge in practices for prevention of pressure ulcer and management nurses face potential and actual barriers during the practice of pressure ulcer prevention heavy work load shortage of staff(40%). Lack of pressure reliving devices (50%) lack of job satisfaction (34%) lack training(28%).Conclusion: So nurses need to get continuing education and training about pressure ulcer prevention that will enhance their knowledge and practices can be improved. Along with reducing barriers which nurses can effectively use their knowledge into practice.